Critical Reading Skill Development through Mobile-Assisted Language Learning (MALL) Collaboration: A Needs Analysis - Rahman Nur, Dedi; Rachman , Dzul; Arbain, Arbain (Universitas Sulawesi Barat, 2026)
This study investigates the integration of collaborative learning within mobile-assisted language learning (MALL) environments to enhance critical reading skills among English Department students in East Kalimantan. The research aims to identify learners’ and lecturers’ needs, wants, and challenges related to critical reading instruction through mobile-based collaboration. Employing a mixed-methods approach, data were collected from 55 students and 5 lecturers using a 50-item Likert-scale questionnaire and semi-structured interviews. Quantitative data were analyzed descriptively, while qualitative responses were coded thematically using ATLAS.ti. The findings reveal that both students and lecturers highly value the incorporation of technology and collaborative activities in fostering critical reading abilities. Over 90% of respondents agreed that MALL enhances engagement, autonomy, and comprehension when combined with peer interaction and authentic materials. However, challenges such as diverse proficiency levels, limited digital resources, and insufficient professional training for lecturers were also identified. The study concludes that designing collaborative MALL frameworks—integrating discussion forums, peer feedback, and adaptive learning tools—can significantly support the development of students’ critical literacy. The results provide a foundation for developing context-specific MALL applications and contribute to the advancement of critical reading pedagogy in higher education